2017
DOI: 10.1007/s00464-017-5727-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following laparoscopic versus open major hepatectomy for hepatocellular carcinoma in patients with cirrhosis: a propensity score-matched analysis

Abstract: BackgroundLaparoscopic major hepatectomy (LMH) for hepatocellular carcinoma (HCC) in patients with cirrhosis remains controversial due to limited reports in the literature. This study analyzed the perioperative and oncological outcomes of LMH for HCC with cirrhosis compared with open major hepatectomy (OMH).MethodsA retrospective analysis of patients with cirrhosis who underwent major hepatectomy for HCC between January 2015 and January 2017 was performed. Patients were divided into the LMH group and the OMH g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
6
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 34 publications
7
66
6
6
Order By: Relevance
“…14); there were no missing studies in the overall morbidity group and the 3-DFS group were identified by the trim-and-fill method using fixed-effect model (Figs. [16][17][18][19][20]. The trend of the results did not change, showing our results were reliable.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…14); there were no missing studies in the overall morbidity group and the 3-DFS group were identified by the trim-and-fill method using fixed-effect model (Figs. [16][17][18][19][20]. The trend of the results did not change, showing our results were reliable.…”
Section: Discussionsupporting
confidence: 58%
“…Through the preliminary search, 990 articles are obtained. After reading titles and abstracts and full texts and removing duplicate documents, 47 articles were included in our study, which involved 5889 patients (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the second ICCLLR, three case‐matched studies with propensity score analysis using Japanese multicentre series or National Clinical Database information demonstrated significantly less intraoperative BL in laparoscopic versus open hepatectomy. However, the intraoperative BL was equivalent for laparoscopic and open hepatectomy in comparative studies using propensity score matching reported from Korea and China, and in an RCT from Norway focusing on minor hepatectomy for colorectal liver metastases.…”
Section: Discussionmentioning
confidence: 96%
“…According to the Second International Consensus Conference for Laparoscopic Liver Resection, minor liver resections, such as left lateral sectionectomy, have become a standard practice, while laparoscopic major liver resections remain in an exploration phase . Furthermore, reports on laparoscopic major hepatectomy from various centers have showed controversial short‐ and long‐term outcomes …”
Section: Introductionmentioning
confidence: 99%